Notes on Kocourekia Bouček (Hymenoptera: Eulophidae: Tetrastichinae) with description of a new species from China - Cao, Huan-Xi; Salle, John La; Fornoff, Felix; Guo, Peng-Fei; Zhu, Chao-Dong (Zootaxa, 2017)
Kocourekia fusis Cao & Zhu sp. n. (Hymenoptera, Eulophidae) is described and illustrated as a parasitoid of aculeate Hymenoptera. Females differ from those of the other two species in Kocourekia by the presence of a malar sulcus, prompting a re-examination of generic limits. A re-definition of Kocourekia is presented, its relationship with other closely allied genera in the Melittobia complex is discussed, and a key to the species of Kocourekia is provided.